Estudio de factibilidad para la producción de estatuas religiosas, elaboradas en fibra de vidrio, en la parroquia El Cisne, del cantón y provincia de Loja - Murquincho Cuenca, Alonso Fabián (2016)
This work was developed in the Parish of Swan, with the aim of making a "Feasibility Study for the production of religious statues, made of fiberglass, the swan in the parish, canton and province of Loja” in order to provide a healthy quality product at affordable prices to meet the needs of citizens. The study begins with the wording of the Summary, Introduction, this followed the Literature Review, which contains all the terms used in this project, and then the detailed methodology was performed. Here are the results of the project were the same as obtained by the application of tools such as surveys and interviews in addition to the collaboration of several people who helped to get the necessary information as consumers, vendors , suppliers, and others is presented , that it helped tremendously to the development stage of the project. It begins with the study of market in which market segmentation for which we use the different tourists visiting the Swan Sanctuary are 2505 people arriving Annual mind was made , this information allowed us to determine the number of surveys that are 287 which were applied in the parish " the Swan" at strategic locations . Then the required demands of the project is determined, the potential demand reaches 4809 representing 81 % of the people that if they buy religious statues Virgin "Swan” . Actual demand is composed by 89 % of respondents would like to acquire religious statues effective demand corresponds to 94% if buy religious statues made of fiberglass. Technical Study was designed to establish the necessary processes, such as product engineering , plant size , in which the installed capacity is 100 % and 95% used is set . It was determined that the annual production of religious statues, for the first year is 713 units and for the fifth year will have to produce 792 units. Then the engineering project was conducted , the production process, in which the steps are as accomplished , to the finished product, the engineer of the plant where the macro and micro localization is determined so that the company will be located in Barrio April 29 between Called Juan Basin and Arris Morales Parish Swan , and the Canton province of Loja. In addition to Conduct a Legal Management Study which the mission, vision and objectives of the Company is defined as well as the corporate organizational structure and function on which develops the corresponding charts and therefore the functions manual also states indicating tasks for each position, the nature of work and the requirements that employees shall exercise such charges . In another development stage of the project Financial Study in which fixed assets are disclosed, deferred assets and working capital or current assets , where they determine that the investment of the project is $ 7.244 The same fund that was performed by a internal source equivalents $ 5,000 69 % between 2 partners . And from an external source of $ 2,244 equivalent to 31% to be accredited by the Bank for 5 years at 11.20 % per annum. In addition, an Operating Budget , which for the first year is $ 48,075.51 it helps to determine the unit cost is $ 67.45 cents was performed. While the retail price is $ 74.19 cents. With a profit margin of 10%, generating sales of $ 52883.06 all in the first year. With this an analysis and classification of costs for each year are performed as in the first and fifth years of project life , with these data the equilibrium point that for the first year is $ 42,890.40 relative was developed sales and 70.73 % in relation to the installed capacity for the 5th . Year is $ 56,755.86 with respect to sales and 70.88 % in relation to the installed capacity, and the State of Income. Finally the financial evaluation was performed using different indicators such as cash flow than for the first year is $ 3,716.42 Net Present Value NPV is $ 5,176.61 which shows that the project is profitable , the period was performed capital recovery is described in which the investment is recovered in 3 years 2 month 19 days. Indicator Value Through Profit Cost is determined that the following result is deducting $ 1.15 cents for every dollar invested is expected a profit of $ 0.10 cents , the Internal Rate of Return is the 23.77 % and sensitivity Analysis indicates that for this project , the sensitivity values are lower than 1, so do not affect changes in project costs and revenues increased by 22% and decreased to 9.80 % respectively. Finally exposed to the conclusions and recommendations which comes after finishing the Thesis Project . So the implementation of the same is recommended considering the results. Major reference sources used to develop this work is presented in some of the literature . Format of the survey and interview used for the collection of information is presented in the Annexes. Finally the index by which readers can follow and find faster the specific item you are looking for in the project.